Pendampingan Implementasi Kurikulum Merdeka di SMP Negeri 37 Pekanbaru - Widiati, Indah; Rahayu, Sri; Istikomah, Endang (UIR Press, 2024)
SMPN 37 Pekanbaru has implemented the Merdeka curriculum but has not been implemented optimally. SMPN 37 Pekanbaru also has driving teachers who can support the implementation of the Merdeka curriculum in schools. However, there are still several things related to the implementation of the Merdeka curriculum that need intensive assistance. This community service activity aims to provide assistance in the implementation of the Merdeka curriculum for teachers at SMP Negeri 37 Pekanbaru. Through assistance in the implementation of the Merdeka curriculum, it is hoped that teachers at SMP Negeri 37 Pekanbaru will have a deeper understanding of the Merdeka curriculum and be ready to implement the Merdeka curriculum properly in the 2023/2024 academic year. This community service activity was carried out at SMPN 37 Pekanbaru with participants, namely 30 teachers of SMPN 37 Pekanbaru. The material in this activity is about aspects of the implementation of the Merdeka curriculum which include KOSP planning, ATP design, learning and assessment planning, use and development of teaching materials. This activity has many benefits for teachers, namely teachers are better prepared to implement the Merdeka curriculum and have the correct understanding and information about the Merdeka curriculum.